History and fiction: El Maranón, a pilgrim text - Salvatierra, María de Fátima (2014)
In this article we try to present some relevant aspects of the fictional nature of El Marañón of Diego de Aguilar y Cordova. To this end, we will make evident the narrator’s discursive strategies, the fictional aspects related to the legends of the New World; and finally, as evidence of Aguilar’s obvious literary work, we want to show the differences regarding to his main reference source. Unlike other contemporary texts that deal with the same adventure of Lope de Aguirre, this work is clearly profiled as an artistic and successfully finished work of the renaissance in Peru.